Disturbance rejection for biped robots during walking and running using control moment gyroscopes. Issue 4 (13th November 2022) - Xu, Haochen; Yu, Zhangguo; Chen, Xuechao; Dong, Chencheng; Chen, Huanzhong; Huang, Qiang
Abstract: Keeping balance in movement is an important premise for biped robots to complete various tasks. Now, the balance control of biped robots mainly depends on the cooperation of various joints of the robot's body. When robots move faster, the adjustment allowance of joints is reduced, and the robot's anti‐disturbance ability will inevitably decline. To solve this problem, the control moment gyroscope (CMG) is creatively used as an auxiliary stabilisation device for fully actuated biped robots and the CMG assistance strategy, which can be integrated into the biped's balance control framework, is proposed. This strategy includes model predictive control module, distribution module, and CMG precession controller. Under the command of it, CMGs can effectively assist the robot in resisting impact and returning to initial positions in time. The results of anti‐impact simulation on the walking and running biped robot prove that, with the help of CMGs, the robot's ability to resist disturbance and remain stable is significantly improved. The cover image is based on the Original Article Disturbance rejection for biped robots during walking and running using control moment gyroscopes by Haochen Xu et al., https://doi.org/10.1049/csy2.12070 .